Computer-Mediated Communication in the Presidential and Vice-Presidential Social Media Campaigns for the 2024 Election - Alhuda, Muhammad Ilham (International Journal of Science and Society, 2025)
This study explores computer-mediated communication in the context of Indonesia's 2024 presidential and vice-presidential election campaign, specifically through the social media platform Instagram. By employing a content analysis methodology, the research aims to uncover the hashtags used in political campaign posts, identify emerging communication patterns, discover key topics discussed, and trace the sentiments underlying these contents. Data is collected from posts containing relevant campaign hashtags on the Instagram platform. The analysis results are expected to provide a deeper understanding of the evolution of political communication in the digital era, particularly in the context of presidential election campaigns. By understanding these communication dynamics, stakeholders, researchers, and the general public are anticipated to respond more effectively to political messages conveyed through social media. The goal is to foster healthy discussion spaces and strengthen democratic participation during the campaign.